Influence of the main gasifier parameters on a real system for hydrogen production from biomass. (27th July 2016) - Moneti, M.; Di Carlo, A.; Bocci, E.; Foscolo, P.U.; Villarini, M.; Carlini, M.
Abstract: The production of hydrogen from waste biomass could play an important role in the world energy scenario if efficient and reliable processes will be developed. Via kinetic and thermodynamic simulation and experimental data system, realized during the European project UNIfHY, to produce pure hydrogen from biomass is analysed. The plant is mainly composed of bubbling fluidized bed gasifier with catalytic filter candles, Water Gas Shift and Pressure Swing Adsorption (PSA). Focussing on the hydrogen production, a sensitivity study was carried out varying parameters as the steam to biomass ratio and the gasifier operating temperature. The results show that the hydrogen yield increases at increasing temperature and steam to biomass ratio, even if the required energy input increases as well. The global efficiency depends substantially on the PSA unit: the off gas of this unit is composed of residual CO, CH4 and H2, that can be burned in the combustor of the dual fluidized bed gasifier to supply the extra-heat to the gasification process avoiding the input of auxiliary fuel. Highlights: Simulations of a fluidised bed gasifier, catalytic filters candles, WGSRs and PSA system were carried out. The hydrogen chemical efficiency was carried out. The influence of the main gasifier parameters (S/B and gasifier temperature) have been taken into account.